MENGUJI KRITIK DALAM BINGKAI REALITAS - Aminullah; Muhith (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Criticism is a fundamental instrument in intellectual and social life; however, in practice, its meaning often shifts from a reflective tool to an expression of subjective interests. This phenomenon becomes problematic when criticism is no longer grounded in factual reality but is driven by emotions, prejudice, or hidden agendas. This study aims to examine the nature of criticism and to test its relevance within the framework of social and intellectual reality. This research employs a qualitative approach using a literature review method by analyzing scholarly works on critical theory, social reality, and public discourse. Data analysis is conducted through content and interpretative analysis to identify the relationship between criticism and the reality that surrounds it. The findings indicate that constructive criticism must be based on rationality, intellectual honesty, and an orientation toward improvement. Criticism detached from reality tends to distort meaning and potentially generate social conflict. This study concludes that sound criticism is not merely an expression of freedom of speech but must be tested through its alignment with reality and moral responsibility.